Recycling method of waste carbon / carbon composite material
By applying solid-phase shear grinding technology in a disc-shaped solid-phase mechanochemical reactor, carbon fibers are stripped from waste carbon/carbon composite materials to prepare functional additives, which solves the problem of difficulty in recycling waste carbon/carbon composite materials. , achieving high-value reuse and performance improvement of materials.
Patent Information
- Application Number
- CN202411402861.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to effectively recycle and reuse waste carbon/carbon composite materials, mainly because carbon fibers and matrix carbon are difficult to separate, resulting in the recycling and treatment method mainly relies on landfill.
A disc-shaped solid-phase mechanochemical reactor is used to perform solid-phase shear grinding technology to peel off carbon fibers from the carbon matrix of waste carbon/carbon composite materials while maintaining the aspect ratio of the carbon fibers to prepare functional additives.
It has achieved the successful recycling and reuse of carbon/carbon composite materials, endowed the polymer materials with functions such as electrical conductivity, thermal conductivity, reinforcement and wear resistance, reduced the amount of carbon fiber, lowered the cost, and improved the compatibility of the materials.
Smart Images

Figure CN119327843A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of recycling carbon / carbon composite materials, and relates to a method for recycling waste carbon / carbon composite materials, and specifically relates to preparing functional additives using waste carbon / carbon composite materials and using the functional additives to give polymer materials functions such as conductivity, heat conduction, reinforcement and wear resistance, and is particularly directed to treating the above-mentioned waste carbon / carbon composite materials using an industrial grinding disc-shaped solid phase force chemical reactor disclosed in Chinese invention patent CN114534660B. Background Art
[0002] Carbon / carbon (C / C) composites are all-carbonaceous multiphase solid materials that are composited through a certain process using carbon fibers and their fabrics as reinforcements and carbonaceous materials such as pyrolytic carbon or asphalt carbon as the matrix. The preparation methods of carbon / carbon composites can be mainly divided into chemical vapor deposition and liquid phase impregnation due to different densification processes. In the chemical vapor deposition method, the matrix carbon and the fiber are tightly combined and the structure is adjustable, which is the preferred method for preparing high-performance carbon / carbon composites. However, the chemical vapor deposition speed is very slow, the preparation cycle is too long, which has a great impact on the material price, and there is a large amount of waste in the manufacturing process. Carbon / carbon composites have the characteristics of low density, high thermal conductivity, low thermal expansion coefficient, and excellent mechanical properties. They are widely used in aerospace, military, nuclear energy and many other fields. Their high hardness, low weight, and excellent mechanical properties at high temperatures make them the best material for manufacturing aircraft and other high-weight vehicle brakes, and they have great development potential.
[0003] With the in-depth research and rapid development of carbon / carbon composite materials, China's carbon / carbon composite material output will reach about 5,500 tons in 2023, a year-on-year increase of 17.02%. However, according to the survey, there are currently no reports on the reuse of waste carbon / carbon composite materials, and it is generally believed that carbon / carbon composite materials cannot be recycled and reused by chemical or pyrolysis methods, and it is difficult to separate carbon fiber and matrix carbon with existing technology, so the main recycling method of this type of material is to use landfill as the foundation for treatment.
[0004] After searching, the Chinese invention patent application "A process for recycling waste carbon-carbon composite materials" (CN113072388A) discloses a process for recycling waste carbon-carbon composite materials. The key points of its technical solution are that the invention uses a 40-100 mesh sieve to remove impurities and dust from the waste cut off during the processing of carbon-carbon composite products, leaving short fibers of moderate length and uniformity, and fully stirring to increase the density range of the short fibers, which is conducive to more uniform densification in the later stage. The thermosetting phenolic resin and the short fibers are evenly mixed and placed in a vulcanizer with a molding mold for heating and step-by-step pressurization. After heating and pressurizing and curing, carbonization and high-temperature treatment are carried out, and the density can reach 1.3g / cm 3 , and then chemical vapor deposition densification can be performed according to actual needs. After the densification is completed, it can be finely processed according to the required size to achieve the recycling of carbon-carbon composite waste, reduce the amount of carbon fiber used, and reduce costs. Recycling carbon-carbon composites reduces waste and reduces costs.
[0005] In the above-mentioned public patent documents, only the carbon fiber waste generated in the carbon / carbon composite material production process is utilized. The technical content is essentially the recycling of carbon fiber, and it does not actually realize the recycling of the waste carbon / carbon composite material itself, nor does it realize the separation of carbon fiber and matrix carbon.
[0006] In this context, it is urgent to develop a new process to recycle carbon / carbon (C / C) composites. In view of this, it is urgent to develop a method for recycling carbon / carbon composites suitable for practical industrial applications to achieve the transformation of waste carbon / carbon composites into treasure and high-value reuse. Summary of the invention
[0007] The present invention aims at the above-mentioned problems in the prior art and provides a method for recycling waste carbon / carbon composite materials, wherein carbon fibers are stripped from the carbon matrix of the waste carbon / carbon composite materials by solid phase shear milling technology, while maintaining the aspect ratio of the carbon fibers to a high degree. Through the technical solution provided by the present invention, carbon / carbon composite materials are successfully recycled and reused for the first time by solid phase shear milling technology, and a new recycling strategy for carbon / carbon composite materials is proposed for the first time.
[0008] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.
[0009] A method for recycling waste carbon / carbon composite materials comprises the following steps:
[0010] (1) treating the waste carbon / carbon composite material, after pretreatment including washing, and crushing it into waste carbon / carbon composite fragments / powder of a size suitable for adding to a millstone-shaped solid phase force chemical reactor for grinding;
[0011] (2) adding the waste carbon / carbon composite powder obtained in step (2) into a millstone-shaped solid phase force chemical reactor for grinding, and after the grinding is completed, collecting the obtained powder to be used as a functional additive for polymer materials;
[0012] The process parameters of the millstone-shaped solid phase force chemical reactor are as follows: the grinding pressure is 3-5 MPa, 0-25°C circulating cooling liquid is introduced to control the temperature of the millstone surface, the cycle grinding is 4-20 times, and the millstone speed is 50-150 rpm.
[0013] The main point of the invention is that for the first time, a purely mechanical recycling method for waste carbon / carbon composite materials is provided through a grinding disc-shaped solid phase mechanochemical reactor, which mainly uses solid phase shear grinding technology to peel carbon fibers from the carbon matrix of waste carbon / carbon composite materials while maintaining the aspect ratio of carbon fibers to a high degree. Through the technical solution provided by the present invention, carbon / carbon composite materials are successfully recycled and reused for the first time through solid phase shear grinding technology, and a new recycling strategy for carbon / carbon composite materials is proposed for the first time.
[0014] In the actual experiment with the number of cyclic grinding as a variable, the powder obtained by grinding was collected through electron microscopy and it was found that when the number of cyclic grinding reached 19 to 20 times, the carbon fiber in the carbon matrix could be more effectively stripped, and the carbon fiber was basically distributed in a single strand, confirming that the present invention achieves the carbon fiber stripping of carbon / carbon composite materials by mechanical means.
[0015] In this article, the waste carbon / carbon composite material described in step (1) is a fully carbonaceous multiphase solid material that is composited through a certain process using carbon fibers and their fabrics as reinforcements and carbonaceous materials such as pyrolytic carbon or asphalt carbon as a matrix in the prior art. Those skilled in the art should recognize that waste carbon / carbon composite materials that meet the above description / definition can be selected as raw materials for recycling in the present invention.
[0016] In order to better illustrate the present invention and provide a technical solution for reference, the waste carbon / carbon composite material in step (1) includes a carbon / carbon composite material with deposited carbon and impregnated carbon as a matrix and different types of carbon fibers as a reinforcement.
[0017] In this article, the pretreatment described in step (1) includes washing, which is mainly to remove impurities on the surface of the waste carbon / carbon composite material. If necessary, the non-carbon / carbon composite material part needs to be removed. Those skilled in the art can carry out specific treatment according to the existing technology based on the actual conditions of the waste carbon / carbon composite material that needs to be reused.
[0018] In this article, the waste carbon / carbon composite fragments / powders processed and crushed to a size suitable for adding to the millstone-shaped solid phase force chemical reactor for grinding are described in step (1). Those skilled in the art can select the appropriate waste carbon / carbon composite fragments / powder size by consulting the following public literature related to the millstone-shaped solid phase force chemical reactor.
[0019] In one of the technical solutions, the waste carbon / carbon composite fragments / powder are processed and crushed to an average particle size of not more than 1.5 cm in step (1).
[0020] The millstone-shaped solid phase force chemical reactor in step (2) is an industrial millstone-shaped solid phase force chemical reactor disclosed in the prior invention patent CN114534660B of the applicant of the present invention.
[0021] It should be noted that the industrial grinding disc-shaped solid-phase force chemical reactor is based on the principle of the force chemical reactor disclosed in the prior authorized patent ZL95111258.9, and is an industrial equipment that was finally improved and launched. It is significantly different from the structure of the laboratory prototype when ZL95111258.9 was applied for. A new grinding disc structure is designed for industrial high-efficiency force chemical grinding treatment. The vertical setting of the grinding disc in the past is improved to a horizontal setting, and the size of the grinding disc is greatly increased. Based on the horizontal setting and large size of the grinding disc, the relevant fixed grinding disc assembly and hydraulic lifting system are innovatively designed, which greatly improves its three-dimensional shear force, and finally successfully realizes the stripping of carbon fibers from the carbon matrix of waste carbon / carbon composite materials while maintaining the aspect ratio of carbon fibers to a high degree.
[0022] Usually, the actual operation of the above-mentioned cycle grinding process is to grind the material through a disc-shaped solid phase force chemical reactor, collect the product at the discharge end and then place it in a disc-shaped solid phase force chemical reactor for grinding again. The above process is regarded as one cycle grinding.
[0023] Herein, in step (2), a circulating cooling liquid at 0 to 25° C. is introduced to control the temperature of the grinding disc surface, and the cooling liquid is water, ethylene glycol or glycerol.
[0024] By using the functional additives provided by the present invention, the polymer material can be endowed with electrical conductivity, thermal conductivity, reinforcement and wear resistance through conventional processing methods such as melt blending, thereby realizing the transformation of waste carbon / carbon composite materials into treasure and high-value recycling.
[0025] In order to better illustrate the present invention and provide a technical solution for reference, the present invention also provides a PA6-based composite material using the functional additive, which mainly includes the following raw material components:
[0026] PA6 (Nylon 6) 70-95 parts,
[0027] 5-30 parts of functional additives,
[0028] The total amount of PA6 and functional additives is 100 parts.
[0029] In one of the technical solutions, the PA6-based composite material is prepared by a twin-screw extrusion process.
[0030] In one preferred technical solution, the preparation method of the PA6-based composite material mainly comprises the following steps: after uniformly mixing the raw material components, processing through a twin-screw extruder to prepare a PA6-based composite material;
[0031] Among them, the temperatures of each zone of the twin-screw extruder were set to 165°C, 190°C, 220°C, 250°C, 250°C, 250°C, 250°C, 245°C, and 240°C, respectively, and the screw speed was maintained at 300rpm.
[0032] In order to better characterize the functionality of the above-mentioned functional additives, in one of the technical schemes, the PA6-based composite material prepared above is prepared into a PA6-based composite product by an injection molding machine, and the temperature of each zone of the injection molding machine from the hopper to the nozzle is controlled at 165°C, 190°C, 250°C, and 250°C, respectively.
[0033] The present invention has the following beneficial effects:
[0034] (1) The present invention provides a method for recycling waste carbon / carbon composite materials, which uses solid phase shear milling technology to peel carbon fibers from the carbon matrix of waste carbon / carbon composite materials while maintaining the aspect ratio of the carbon fibers to a high degree. Through the technical solution provided by the present invention, carbon / carbon composite materials are successfully recycled and reused for the first time through solid phase shear milling technology, and a new recycling strategy for carbon / carbon composite materials is proposed for the first time.
[0035] (2) The present invention provides a method for recycling waste carbon / carbon composite materials. The functional additives prepared using the waste carbon / carbon composite materials can impart electrical conductivity, thermal conductivity, reinforcement and wear resistance to polymer materials, thereby realizing the transformation of waste carbon / carbon composite materials into treasure and high-value recycling.
[0036] (3) The present invention provides a method for recycling waste carbon / carbon composite materials. The functional additives prepared using the waste carbon / carbon composite materials have an increased surface roughness, which is beneficial for interaction with the polymer matrix and improves the compatibility of the prepared composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1The electron microscope photos of the functional additives and the waste carbon / carbon wear-resistant composite material raw materials prepared in Examples 1 to 4 and Comparative Example 1, and the EDS, thermal conductivity and electrical conductivity comparison diagrams. In the figure, Figure a is an electron microscope photo of the waste carbon / carbon wear-resistant composite material raw material; Figure b is an electron microscope photo of the functional additive prepared in Comparative Example 1; Figure c is an electron microscope photo of the functional additive prepared in Example 4; Figure d is an electron microscope photo of the functional additive prepared in Example 3; Figure e is an electron microscope photo of the functional additive prepared in Example 2; Figure f is an electron microscope photo of the functional additive prepared in Example 1; CFCM in Figures (g) and (i) is the corresponding waste carbon / carbon wear-resistant composite material raw material.
[0038] Figure 2 The DSC curves and TGA curves of the PA6-based composite splines and pure PA6 prepared in Examples 1 to 4 and Comparative Example 1 are shown. Among them, Figure (a) is a DSC crystallization curve; Figure (b) is a DSC heating curve; Figures (c) and (d) are TGA test result curves.
[0039] Figure 3 The cross-sectional SEM morphology images of the PA6-based composite splines and pure PA6 prepared in Examples 1 to 4 and Comparative Example 1 are shown. Among them, Figure a is a cross-sectional SEM morphology image of pure PA6; Figure b is a cross-sectional SEM morphology image of the PA6-based composite spline prepared in Comparative Example 1; Figure c is a cross-sectional SEM morphology image of the PA6-based composite spline prepared in Example 4; Figure d is a cross-sectional SEM morphology image of the PA6-based composite spline prepared in Example 3; Figure e is a cross-sectional SEM morphology image of the PA6-based composite spline prepared in Example 2; Figure f is a cross-sectional SEM morphology image of the PA6-based composite spline prepared in Example 1.
[0040] Figure 4 It is a bar graph showing the tensile (a) and impact (b) test results of the PA6-based composite strips prepared in Examples 1 to 4 and Comparative Example 1 and pure PA6.
[0041] Figure 5 The thermal conductivity (a) and heat deformation temperature (b) of the PA6-based composite strips prepared in Examples 1 to 4 and Comparative Example 1 and pure PA6 are shown in the figure.
[0042] Figure 6The results of the sliding friction coefficient of the PA6-based composite strips and pure PA6 against steel balls prepared in Examples 1 to 4 and Comparative Example 1 and the electron microscope images of the worn surfaces are shown. Among them, Figure (a) is a bar graph of the average friction coefficient against steel balls; Figure (b) is a curve graph of the real-time friction coefficient against steel balls; Figure c is an electron microscope image of the worn surface of pure PA6; Figure d is an electron microscope image of the worn surface of the PA6-based composite strips prepared in Comparative Example 1; Figure e is an electron microscope image of the worn surface of the PA6-based composite strips prepared in Example 3; Figure f is an electron microscope image of the worn surface of the PA6-based composite strips prepared in Example 2; Figure g is an electron microscope image of the worn surface of the PA6-based composite strips prepared in Example 1. DETAILED DESCRIPTION
[0043] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0044] A method for recycling waste carbon / carbon composite materials comprises the following steps:
[0045] (1) treating the waste carbon / carbon composite material, after pretreatment including washing, and crushing it into waste carbon / carbon composite fragments / powder of a size suitable for adding to a millstone-shaped solid phase force chemical reactor for grinding;
[0046] (2) adding the waste carbon / carbon composite powder obtained in step (2) into a millstone-shaped solid phase force chemical reactor for grinding, and after the grinding is completed, collecting the obtained powder to be used as a functional additive for polymer materials;
[0047] The process parameters of the millstone-shaped solid phase force chemical reactor are as follows: the grinding pressure is 3-5 MPa, 0-25°C circulating cooling liquid is introduced to control the temperature of the millstone surface, the cycle grinding is 4-20 times, and the millstone speed is 50-150 rpm.
[0048] The main point of the invention is that for the first time, a purely mechanical recycling method for waste carbon / carbon composite materials is provided through a grinding disc-shaped solid phase mechanochemical reactor, which mainly uses solid phase shear grinding technology to peel carbon fibers from the carbon matrix of waste carbon / carbon composite materials while maintaining the aspect ratio of carbon fibers to a high degree. Through the technical solution provided by the present invention, carbon / carbon composite materials are successfully recycled and reused for the first time through solid phase shear grinding technology, and a new recycling strategy for carbon / carbon composite materials is proposed for the first time.
[0049] In the actual experiment with the number of cyclic grinding as a variable, the powder obtained by grinding was collected through electron microscopy and it was found that when the number of cyclic grinding reached 19 to 20 times, the carbon fiber in the carbon matrix could be more effectively stripped, and the carbon fiber was basically distributed in a single strand, confirming that the present invention achieves the carbon fiber stripping of carbon / carbon composite materials by mechanical means.
[0050] In this article, the waste carbon / carbon composite material described in step (1) is a fully carbonaceous multiphase solid material that is composited through a certain process using carbon fibers and their fabrics as reinforcements and carbonaceous materials such as pyrolytic carbon or asphalt carbon as a matrix in the prior art. Those skilled in the art should recognize that waste carbon / carbon composite materials that meet the above description / definition can be selected as raw materials for recycling in the present invention.
[0051] In order to better illustrate the present invention and provide an implementation method for reference, the waste carbon / carbon composite material in step (1) includes a carbon / carbon composite material with deposited carbon and impregnated carbon as a matrix and different types of carbon fibers as reinforcement.
[0052] In this article, the pretreatment described in step (1) includes washing, which is mainly to remove impurities on the surface of the waste carbon / carbon composite material. If necessary, the non-carbon / carbon composite material part needs to be removed. Those skilled in the art can carry out specific treatment according to the existing technology based on the actual conditions of the waste carbon / carbon composite material that needs to be reused.
[0053] In this article, the waste carbon / carbon composite fragments / powders processed and crushed to a size suitable for adding to the millstone-shaped solid phase force chemical reactor for grinding are described in step (1). Those skilled in the art can select the appropriate waste carbon / carbon composite fragments / powder size by consulting the following public literature related to the millstone-shaped solid phase force chemical reactor.
[0054] In one embodiment, the waste carbon / carbon composite fragments / powder are processed and crushed to an average particle size of no more than 1.5 cm in step (1).
[0055] The millstone-shaped solid phase force chemical reactor in step (2) is an industrial millstone-shaped solid phase force chemical reactor disclosed in the prior invention patent CN114534660B of the applicant of the present invention.
[0056] It should be noted that the industrial grinding disc-shaped solid-phase force chemical reactor is based on the principle of the force chemical reactor disclosed in the prior authorized patent ZL95111258.9, and is an industrial equipment that was finally improved and launched. It is significantly different from the structure of the laboratory prototype when ZL95111258.9 was applied for. A new grinding disc structure is designed for industrial high-efficiency force chemical grinding treatment. The vertical setting of the grinding disc in the past is improved to a horizontal setting, and the size of the grinding disc is greatly increased. Based on the horizontal setting and large size of the grinding disc, the relevant fixed grinding disc assembly and hydraulic lifting system are innovatively designed, which greatly improves its three-dimensional shear force, and finally successfully realizes the stripping of carbon fibers from the carbon matrix of waste carbon / carbon composite materials while maintaining the aspect ratio of carbon fibers to a high degree.
[0057] Usually, the actual operation of the above-mentioned cycle grinding process is to grind the material through a disc-shaped solid phase force chemical reactor, collect the product at the discharge end and then place it in a disc-shaped solid phase force chemical reactor for grinding again. The above process is regarded as one cycle grinding.
[0058] Herein, in step (2), a circulating cooling liquid at 0 to 25° C. is introduced to control the temperature of the grinding disc surface. In one embodiment, the cooling liquid is water, ethylene glycol or glycerol.
[0059] In one embodiment, the process parameters of the millstone-shaped solid phase force chemical reactor in step (2) are: the grinding pressure is 3-5MPa, for example, 3MPa, 3.5MPa, 4MPa, 4.5MPa, 5MPa or any range or point value therebetween; the temperature of the millstone surface is controlled by passing a circulating cooling liquid at 0-25°C, for example, 0°C, 4°C, 5°C, 8°C, 10°C, 12°C, 14°C, 16°C, 18°C, 20°C, 22°C, 24°C, 25°C or any range or point value therebetween; any range or point value between; cycle grinding 4 to 20 times, for example 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times, 20 times; grinding disc speed 50 to 150 rpm, for example 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm, 150 rpm.
[0060] By using the functional additives provided by the present invention, the polymer material can be endowed with electrical conductivity, thermal conductivity, reinforcement and wear resistance through conventional processing methods such as melt blending, thereby realizing the transformation of waste carbon / carbon composite materials into treasure and high-value recycling.
[0061] In order to better illustrate the present invention and provide an embodiment for reference, the present invention also provides a PA6-based composite material using the functional additive, which mainly includes the following raw material components:
[0062] PA6 (Nylon 6) 70-95 parts,
[0063] 5-30 parts of functional additives,
[0064] The total amount of PA6 and functional additives is 100 parts.
[0065] In one embodiment, the PA6-based composite material is prepared by a twin-screw extrusion process.
[0066] In one preferred embodiment, the preparation method of the PA6-based composite material mainly comprises the following steps: after uniformly mixing the raw material components, processing through a twin-screw extruder to prepare a PA6-based composite material;
[0067] Among them, the temperatures of each zone of the twin-screw extruder were set to 165°C, 190°C, 220°C, 250°C, 250°C, 250°C, 250°C, 245°C, and 240°C, respectively, and the screw speed was maintained at 300rpm.
[0068] In order to better characterize the functionality of the above-mentioned functional additives, in one of the technical schemes, the PA6-based composite material prepared above is prepared into a PA6-based composite product by an injection molding machine, and the temperature of each zone of the injection molding machine from the hopper to the nozzle is controlled at 165°C, 190°C, 250°C, and 250°C, respectively.
[0069] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0070] Example
[0071] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0072] 1. Raw materials
[0073] Waste carbon / carbon wear-resistant composite materials (CFCM) were provided by Xi'an Aviation Brake Technology Co., Ltd.;
[0074] Nylon 6 (PA6) (B30S) was purchased from LANXESS.
[0075] 2. Preparation method
[0076] (1) After pretreatment including washing, the waste carbon / carbon wear-resistant composite material (CFCM) is crushed into waste carbon / carbon composite fragments with an average particle size of no more than 1 cm by a 5.5 kW high-power crusher;
[0077] (2) adding the waste carbon / carbon composite powder obtained in step (2) into a millstone-shaped solid phase force chemical reactor for grinding, and after the grinding is completed, collecting the obtained powder to be used as a functional additive for polymer materials;
[0078] The process parameters of the millstone-shaped solid phase force chemical reactor are as follows: the grinding pressure is 3 MPa, 25° C. circulating cooling liquid is introduced to control the temperature of the millstone surface, the cycle grinding is 4 to 20 times, and the millstone speed is 100 rpm.
[0079] In order to facilitate performance verification, the method for preparing PA6-based composite splines using the functional additive mainly includes the following steps:
[0080] (I) By weight, the raw material components are mixed uniformly according to the following proportions to prepare a mixed material:
[0081] PA6 (Nylon 6) 70 parts,
[0082] 30 parts of functional additives;
[0083] (II) processing the mixed material obtained in step (I) through a twin-screw extruder to prepare a PA6-based composite material;
[0084] Among them, the temperature of each zone of the twin-screw extruder was set at 165°C, 190°C, 220°C, 250°C, 250°C, 250°C, 250°C, 245°C, and 240°C, respectively, and the screw speed was maintained at 300rpm;
[0085] (III) preparing the PA6-based composite material obtained in step (II) into PA6-based composite strips by using an injection molding machine;
[0086] Among them, the temperature of each zone of the injection molding machine from the hopper to the nozzle is controlled at 165℃, 190℃, 250℃, and 250℃ respectively.
[0087] 3. Test Methods
[0088] Scanning electron microscopy (SEM-450, FEI instrument Co., USA) was used to observe the fiber stripping, aspect ratio, dispersion of the functional additives and the wear surface morphology of the PA6-based composite specimens. The functional additives were analyzed by energy dispersive x-ray (EDX) elemental composition analyzer. The cross-section of the PA6-based composite specimens needed to be brittle fractured in liquid nitrogen, and all samples were gold-sprayed before testing.
[0089] Thermal conductivity of PA6 based composite strips was measured using a thermal conductivity meter (Hot Disk TPS2500S), and the sensor was placed between two identical strips. The strips were tightened to provide good contact with the sensor.
[0090] The electrical properties of unmilled functional additives and those milled at different times were compared using the four-probe method. The conductivity was tested at 15 pressure points in the range of 2MPa-30MPa and compared at the same pressure.
[0091] Differential scanning calorimeter (Q20, TAInstruments, USA) was used to study the melting and crystallization behaviors of PA6-based composite strips. The test temperature range was 40-250°C, the heating (cooling) rate was 10°C / min, and the thermal history of the sample was eliminated by keeping it at 200°C for 5 minutes. The DSC curve of the PA6-based composite strips was measured in a nitrogen atmosphere.
[0092] The thermal stability of PA6 composite strips in air and nitrogen atmosphere was determined by thermogravimetric analyzer (Q50, TA Instruments, USA) in the temperature range of 40-700°C and the heating rate of 10°C / min.
[0093] Wear tests were performed on a Bruker UMT-3Tribometer (Bellerica, MA, USA) using a GCr15 stainless steel ball sliding on the surface of a PA6-based composite specimen. A stainless steel ball with a diameter of 4.75 mm was mounted on a bracket connected to a three-dimensional force sensor, and the sample was tested using a ball-on-disk instrument. The normal load applied was 10 N, and the wear test was performed for 6000 cycles under dry conditions.
[0094] The tensile and bending properties of PA6 composite strips were tested using a universal material testing machine (Instron 5576, USA) according to ASTM Standard D638-10 and ASTM Standard D790-10. The impact test was performed using a plastic pendulum impact tester (PIT 501J, Shenzhen Wance Equipment Co., Ltd.) according to ASTM D6110-2010.
[0095] The heat deformation temperature of PA6-based composite specimens was tested using a heat deformation temperature tester (HDV2, Atlas, Sweden) with a load of 1.8 MPa.
[0096] Example 1
[0097] In Example 1, a functional additive and a PA6-based composite strip were prepared according to the above "2. Preparation method", and the cyclic grinding in step (2) was 19 times. The prepared functional additive was recorded as CFCM-20, and the PA6-based composite strips were recorded as PA6 / CFCM-20 and S3M-20. The test was carried out according to the above "3. Test method".
[0098] Example 2
[0099] In Example 2, a functional additive and a PA6-based composite strip were prepared according to the above "2. Preparation method", and the cyclic grinding in step (2) was 14 times. The prepared functional additive was recorded as CFCM-20, and the PA6-based composite strips were recorded as PA6 / CFCM-15 and S3M-15. The tests were carried out according to the above "3. Test method".
[0100] Example 3
[0101] In Example 3, a functional additive and a PA6-based composite strip were prepared according to the above "2. Preparation method", and the cyclic grinding in step (2) was 9 times. The prepared functional additive was recorded as CFCM-20, and the PA6-based composite strips were recorded as PA6 / CFCM-10 and S3M-10. The test was carried out according to the above "3. Test method".
[0102] Example 4
[0103] In Example 4, a functional additive and a PA6-based composite strip were prepared according to the above "2. Preparation method", and the cyclic grinding in step (2) was performed 4 times. The prepared functional additive was recorded as CFCM-20, and the PA6-based composite strips were recorded as PA6 / CFCM-5 and S3M-5. The test was carried out according to the above "3. Test method".
[0104] Comparative Example 1
[0105] In Comparative Example 1, the waste carbon / carbon composite fragments processed and crushed according to step (1) of the above "2. Preparation method" are directly used as functional additives for comparison, and PA6-based composite strips are prepared according to steps (I) to (III) for comparison. The prepared functional additive is recorded as CFCM-0, and the PA6-based composite strips are recorded as PA6 / CFCM-0 and S3M-0, and are tested according to the above "3. Test method".
[0106] 4. Test Results
[0107] like Figure 1 As shown in Figure 2, the changes in the morphology of CFCM during the solid phase shear milling technique were evaluated by scanning electron microscopy (SEM) observation. Figure 1 From a to f, it can be clearly seen that the carbon fibers in CFCM-0 are uniformly wrapped in the carbon matrix, and after the crushing process, the particle size of CFCM particles is relatively large, and a large amount of carbon matrix is still wrapped on the surface and inside of the carbon fiber bundle, making it basically impossible to separate them. CFCM is subjected to strong three-dimensional shearing during the grinding process. The solid-phase shear grinding technology can effectively realize the stripping of carbon fibers from the carbon matrix and maintain its aspect ratio to the greatest extent. With the increase of the number of cyclic grinding cycles, the bundled carbon fiber bundles are further dissociated, the average fiber length decreases, the surface roughness increases, and some narrow grooves are distributed parallel to the longitudinal direction of the fiber. When the number of cyclic grinding cycles increases to 19, the stripping of carbon fibers in the carbon matrix can be effectively achieved, and the carbon fibers are basically distributed as single strands. The EDS results are shown in Figure 1 As shown in (g), both crushing and grinding can increase the oxygen content on the surface of CFCM, providing potential value for further application of CFCM in the future.
[0108] The thermal and electrical conductivity of the sample are Figure 1 As shown in (h) and (i), after grinding, the thermal conductivity of the sample decreased from 0.30 W / mk to 0.21 W / mk, and the electrical conductivity decreased from 332.31 S / cm to 109.38 S / cm, but overall it was able to remain consistent with the sample that was only crushed, indicating that grinding did not cause significant damage to the aspect ratio of its carbon fiber.
[0109] like Figure 2 As shown, the DSC curve of the obtained PA6-based composite spline is as follows Figure 2 (a), (b), compared with the crystallinity of pure PA6, it can be concluded that the introduction of CFCM can improve the crystallinity of the composite material, which is beneficial to improving the mechanical properties of the composite material.
[0110] Figure 2 (c) and (d) show the TGA results of PA6 and PA6-based composite strips, and the test was carried out under the conditions of 40-700 ° C. According to the TGA curve analysis, the maximum mass loss occurred between 355 and 465 ° C, and the thermal stability improvement was not significant. During the test, PA6 was almost completely consumed, and the residual weight of the composite material after adding 30wt% functional additives was basically consistent with the weight percentage of CFCM contained in the particles, but the residual carbon of the S3M-20 sample increased, indicating that it can promote carbonization.
[0111] Figure 3This is the SEM morphology of the cross-section of the PA6-based composite spline. The microstructure of the PA6-based composite spline after injection molding is composed of PA6 matrix and carbon fiber. As the number of grinding cycles increases, the carbon fiber bundles gradually disappear, and the carbon fibers can be evenly dispersed in the PA6 matrix.
[0112] Figure 4 The tensile and impact test results of PA6-based composite strips show that in Comparative Example 1, the elongation at break of PA6-based composite strips decreased from 39.37% to 8.22%, and the impact strength decreased from 7.87KJ / m 2 Reduced to 2.13KJ / m 2 , and the tensile strength increased from 64.35MPa to 72.79MPa. With the solid phase milling of CFCM and the increase in the number of milling cycles, the tensile strength and impact strength of the composite material gradually increased. After 19 cycles of milling, the tensile strength and impact strength of the PA6-based composite strips increased by 14.49% and 93.43% respectively compared with the PA6-based composite comparison strips. With the increase in the number of cyclic milling, the degree of fiber peeling and surface roughness of CFCM increased, resulting in an increase in the contact area between a single fiber and the PA6 matrix, which further led to an enhanced interface bonding between the fiber and the matrix. This result is conducive to the stress transfer between the filler and the matrix under the action of external force, and improves the tensile strength and impact strength of the composite material.
[0113] like Figure 5 As shown, the thermal conductivity of PA6-based composite splines is Figure 5 As shown in (a), after adding functional additives, the thermal conductivity increases from the original 0.211W / mK to 0.611W / mK. The increase in the thermal conductivity of the composite material can effectively reduce the maximum temperature of the contact surface during high-speed friction and avoid the aggravation of wear caused by surface softening. As the number of cyclic grinding increases, the thermal conductivity of the composite material only decreases slightly.
[0114] Heat deformation temperature (HDT) is one of the main indicators to measure the heat resistance of plastics. Improving the heat deformation temperature of composite materials is beneficial to the recycling of PA6-based composite materials. Figure 5 (b) shows the effect of cyclic milling on the HDT of PA6-based composite strips. The HDT of PA6 is about 47.2°C, and the HDT of the comparative example 1 sample increases to 108.2°C. As the number of cyclic milling increases, the HDT gradually increases to 114.6°C, and then decreases to 97.3°C at 19 cyclic milling. Compared with pure PA6, the HDT increases by up to 67.4°C. This is attributed to the fiber reinforcement effect. The carbon fibers in the added functional additives can resist the three-point bending load applied during the measurement. The HDT of the composite material increases after milling because the reinforcing fibers with a higher aspect ratio can more effectively transfer the applied load to adjacent fibers through the matrix.
[0115] COF of pure PA6 and PA6-based composite splines sliding against steel balls under dry linear reciprocating sliding conditions Figure 6 As shown. The transient COF fluctuates greatly with the sliding distance, which is caused by the wear debris generated during the friction process. Compared with pure PA6, the average COF of the composite material decreases from 0.51 to 0.36, which is about 25.4%. This is because CFCM, as a reinforcement, improves the deformation and plowing resistance of the composite material.
[0116] Secondly, the morphology of the worn surface of the PA6-based composite spline was analyzed by scanning electron microscopy, and its morphological properties and wear mechanism were studied. Wear marks caused by steel ball friction can be observed on the PA6 surface, and debris exists on the worn surface. This is due to the poor self-lubricating property of PA6. The wear during the friction process is mainly caused by fatigue caused by the corrosive damage of the hard counterpart. From the morphology of the worn surface of the PA6-based composite spline shown, a small amount of carbon fiber is exposed on the friction surface, which indicates that the fiber bears most of the normal load, which is conducive to reducing the wear rate. Under the action of mechanical external force, cracks can be observed at the fiber-matrix boundary. The wear debris of the PA6 matrix may be deformed and transferred back to the wear surface. These fragments repair the fiber / matrix interface to a certain extent by filling the cracks / cavities on the wear surface, forming a friction surface and reducing the friction coefficient.
[0117] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for recycling waste carbon / carbon composite materials, characterized in that The following steps are involved: (1) treating the waste carbon / carbon composite material, after pretreatment including washing, and crushing it into waste carbon / carbon composite fragments / powder of a size suitable for adding to a millstone-shaped solid phase force chemical reactor for grinding; (2) adding the waste carbon / carbon composite powder obtained in step (2) into a millstone-shaped solid phase force chemical reactor for grinding, and after the grinding is completed, collecting the obtained powder to be used as a functional additive for polymer materials; The process parameters of the millstone-shaped solid phase force chemical reactor are as follows: the grinding pressure is 3-5 MPa, 0-25°C circulating cooling liquid is introduced to control the temperature of the millstone surface, the cycle grinding is 4-20 times, and the millstone speed is 50-150 rpm.
2. The recycling method according to claim 1, characterized in that: The waste carbon / carbon composite fragments / powder processed and crushed to an average particle size of no more than 1.5 cm in step (1).
3. The functional additive prepared by the method for recycling waste carbon / carbon composite materials as described in claim 1.
4. The functional additive as claimed in claim 3 is used in the preparation of polymer materials.
5. A PA6-based composite material using the functional additive according to claim 3, characterized in that Mainly includes the following raw material components: PA6 70~95 parts, 5-30 parts of functional additives, The total amount of PA6 and functional additives is 100 parts.
6. The PA6-based composite material according to claim 5, characterized in that The preparation method mainly comprises the following steps: After the raw material components are uniformly mixed, they are processed by a twin-screw extruder to prepare a PA6-based composite material; Among them, the temperatures of each zone of the twin-screw extruder were set to 165°C, 190°C, 220°C, 250°C, 250°C, 250°C, 250°C, 245°C, and 240°C, respectively, and the screw speed was maintained at 300rpm.
7. A PA6-based composite product using the PA6-based composite material according to claim 5, characterized in that: The PA6-based composite material was prepared into a PA6-based composite product by an injection molding machine, and the temperature of each zone of the injection molding machine from the hopper to the nozzle was controlled at 165°C, 190°C, 250°C, and 250°C, respectively.
Citation Information
Patent Citations
Mechanico-chemical reactor
CN1130545A
Process method for recycling carbon-carbon composite material waste
CN113072388A
An industrial millstone-shaped solid-phase mechanochemical reactor
CN114534660B
Method for regenerating carbon fibers from carbon fiber-reinforced composite material wastes
CN107082584A
Recovery method of fiber reinforced composite material
CN111171373A
Cited By
Continuous preparation device for phenolic resin carbon material
CN120838809A
Continuous phenolic resin carbon material production device
CN120838809B
SiC-reinforced high-heat-resistance regenerated CFCM composite material and preparation method thereof
CN121377805A